VD_FINDINFO HC / 2013 / 431 vom 17. Juni 2013 - VD Tribunal cantonal (2013)
CONTRAT DE TRAVAIL, RÉSILIATION IMMÉDIATE, JUSTE MOTIF, INDEMNITÉEN GÉNÉRAL | 337 al. 1 CO, 337 al. 2 CO, 337 al. 3 CO, 337 CO, 337c al. 1 CO, 337c al. 2 CO, 337c al. 3 CO, 337c CO